The effect of implant placement torque on crestal bone remodeling after 1 year of loading - Aldahlawi S; Demeter A; Irinakis T (Dove Medical Press, 2018)
Salwa Aldahlawi,1 Angela Demeter,2 Tassos Irinakis3 1Department of Basic and Clinical Oral Sciences, College of Dentistry, Umm Al-Qura University, Mecca, Saudi Arabia; 2Private Practice, Calgary, Alberta, Canada; 3Graduate Periodontic Program, Faculty of Dentistry, University of British Columbia, Vancouver, British Columbia, Canada Purpose: The aim of this study was to evaluate and compare crestal bone levels (CBLs) after 1 year of loading of self-tapping bone condensing implants placed with high insertion torque (IT) compared to those placed with lower IT. Materials and methods: A retrospective chart review of 66 consecutive patients who received at least one self-tapping bone condensing implant and were in function for at least 1 year was conducted. On the basis of intrasurgical notes documenting the implant IT, the patient population was divided into group A (implant IT, >55 Ncm) and group B (IT, <55 Ncm). Radiographs taken immediately after insertion and during annual follow-up appointments were evaluated for detecting crestal bone loss. The relationship between IT and crestal bone loss, bone density, and jaw location were analyzed, and a P-value of 0.05 was considered to be statistically significant. Results: A total of 113 self-tapping bone condensing NobelActiveTM implants were placed. The average follow-up period from the placement of the implant restoration was 12.87 (±4.83) months. Six implants were classified as failures resulting in overall survival rate of 94.6%. Implants in group A had a mean IT of 67.35 ± 4.0 Ncm, whereas implants in the group B had a mean IT of 37.9 ± 12.62 Ncm. Implants in group A had statistically significant crestal bone loss compared to implants in group B (0.95 ± 1.60 and 0.18 ± 0.68 mm, respectively). Group A implants placed in the mandible showed significantly more pronounced crestal bone loss (2.12 ± 1.99 mm) compared to those placed in the maxilla (0.25 ± 0.65 mm; P<0.05); however, this was not the case in group B implants. Conclusion: Implants inserted with high IT (>55 Ncm) showed more peri-implant bone remodeling than implants inserted with a less assertive IT (<55 Ncm). Bone density and jaw location affect IT and CBLs. Keywords: dental implant, nobelactive, insertion torque, torque, crestal bone level, marginal bone level